(untitled) (REMUNOM, 2025)
This study analyzed the conditions, organization, and socio-professional relationships of work and their impacts on the health and well-being of public servants, with an emphasis on the context of the Judiciary. A literature review was conducted in the SciELO and CAPES databases. The combinations of terms used to search for articles were: illness and professional environment and psychological well-being and management or prevention. In total, 13 studies were selected, including 4 dissertations. The results indicate that task overload, lack of institutional recognition, moral harassment, and hierarchical rigidity are the main elements associated with common mental disorders, anxiety, depression, and burnout syndrome. It was evident that technological advancement and teleworking, while promoting flexibility, intensify social isolation and weaken professional bonds. It is concluded that promoting mental health in the public service requires integrated and permanent institutional policies focused on prevention, support, and appreciation of public servants. Among the observed gaps, the scarcity of longitudinal empirical studies and the absence of intersectional analyses that consider gender, race, and specific working conditions stand out. It is recommended that future research explore the impact of mental health policies and humanized management practices on the well-being and quality of life of public servants